2002
DOI: 10.1016/s0037-0738(02)00261-0
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the late Pleistocene stratigraphy of Bermuda

Abstract: The Quaternary stratigraphy of Bermuda is one of the world's most complete sedimentary records of interglacial highstands, representing at least the past million years. Yet in terms of the last interglacial (Rocky Bay Formation), marine isotope substage (MIS) 5e, only scanty deposits are preserved. In contrast, MIS 7, generally regarded as a diminutive interglaciation, exposes widespread emergent subtidal deposits of the Belmont Formation indicating a prolonged sea level highstand at ca. + 2.5 F 0.3 m. This ''… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 41 publications
7
74
0
2
Order By: Relevance
“…Sea level was well above the platform margin, however, as platform flooding is required for substantial bioclastic sediment formation and subsequent transport to the shore (, 220 m). These observations are supported by previous studies on Bermuda that identified a sea level during MIS 5c at , 210 to 215 m (Vollbrecht, 1990;Hearty, 2002).…”
Section: Sedimentology and Aminostratigraphy Of The Enclosing Sedimentssupporting
confidence: 90%
See 4 more Smart Citations
“…Sea level was well above the platform margin, however, as platform flooding is required for substantial bioclastic sediment formation and subsequent transport to the shore (, 220 m). These observations are supported by previous studies on Bermuda that identified a sea level during MIS 5c at , 210 to 215 m (Vollbrecht, 1990;Hearty, 2002).…”
Section: Sedimentology and Aminostratigraphy Of The Enclosing Sedimentssupporting
confidence: 90%
“…This lithologic unit correlates with the Hungry Bay Formation (HBF), formerly the Pembroke Member of the Rocky Bay Formation (Table 1; Fig. 3) (see discussion in Hearty, 2002). The Charles Island deposits yield an equivalent WR mean of 0.27 6 0.01 (N 5 2).…”
Section: Sedimentology and Aminostratigraphy Of The Enclosing Sedimentsmentioning
confidence: 78%
See 3 more Smart Citations